Global Economic Inequality: A Review of International Law on the Mechanism and Fairness of Free Trade Regulation - Bayu Krisnamurti; Dinda Ayu Hapsari (Yayasan Insan Mulia Bima, 2024)
Global economic inequality has become a fundamental problem in an increasingly complex international trade order. This research aims to analyse the impact of free trade regulations on inter-national economic disparities, with a primary focus on the perspective of international law. Through a juridical-normative approach and comparative studies, the research investigates the mechanisms of international law that affect the distribution of economic benefits among developed and developing countries. The research methodology uses normative legal research methods with data collection techniques through literature study, international document analysis, and review of multilateral trade agreements. Primary data sources include international conventions, trade agreements, and official documents of global trade organisations, while secondary sources include legal literature, academic journals, and reports of international institutions. The results reveal that current free trade regulations tend to discriminate against developing countries, with mechanisms that do not fully take into account the principles of substantive justice. The international trade regime still provides a structural advantage to developed countries, creating a cycle of economic dependency to the detriment of developing countries. Critical analyses show that the current international legal framework has not been able to fully bridge the global economic divide. This research proposes the development of a trade regulation model that is more responsive to different levels of economic development, with fairer compensation and protection mechanisms. Key recommendations include: (1) adjustment of clauses in international trade agreements, (2) establishment of a dynamic system of preferences, and (3) institutional strengthening for more equitable monitoring and dispute settlement. The research conclusion confirms the urgency of transforming the paradigm of international trade law towards a more inclusive and equitable system, taking into account the balance of interests between countries and promoting sustainable economic development.